Drug development concerning metallo-β-lactamases in gram-negative bacteria - Li, Xiuyun; Zhao, Jing; Zhang, Bin; Duan, Xuexia; Jiao, Jin; Wu, Weiwei; Zhou, Yuxia; Wang, Hefeng (Frontiers in Microbiology, 2022)
β-Lactams have been a clinical focus since their emergence and indeed act as a powerful tool to combat severe bacterial infections, but their effectiveness is threatened by drug resistance in bacteria, primarily by the production of serine- and metallo-β-lactamases. Although once of less clinical relevance, metallo-β-lactamases are now increasingly threatening. The rapid dissemination of resistance mediated by metallo-β-lactamases poses an increasing challenge to public health worldwide and comprises most existing antibacterial chemotherapies. Regrettably, there have been no clinically available inhibitors of metallo-β-lactamases until now. To cope with this unique challenge, researchers are exploring multidimensional strategies to combat metallo-β-lactamases. Several studies have been conducted to develop new drug candidates or calibrate already available drugs against metallo-β-lactamases. To provide an overview of this field and inspire more researchers to explore it further, we outline some promising candidates targeting metallo-β-lactamase producers, with a focus on Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii. Promising candidates in this review are composed of new antibacterial drugs, non-antibacterial drugs, antimicrobial peptides, natural products, and zinc chelators, as well as their combinations with existing antibiotics. This review may provide ideas and insight for others to explore candidate metallo-β-lactamases as well as promote the improvement of existing data to obtain further convincing evidence.